IMPULSIVE BUYING PADA MAHASISWA PENGGUNA INSTAGRAM - Farichah Nurus Syifa (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The lifestyle of hedonism is mushrooming among students due to the high intensity in using social media. Social media is used as a promotional media of products, thus resulting in the frequent appearance of advertisements on social media one of them instagram. The study aims to find out impulsive buying in student instagram users. The sample from this study is a student of Islamic psychology IAIN Surakarta class of 2018. Research using qualitative methods and research results are presented in qualitative descriptive form. The results showed someone impulsively buying a product that supports the style of life informant with a price of â‰¤ Rp. 150,000. Impulsive buying appears when scrolling up ads on Instagram. So it raises curiosity marked by following the online shop account. Therefore encourage informants to buy products as self-fertiliser. Hedonic motivation becomes one of the driving forces for someone to make purchases based on desire without paying attention to aspect of rationality.